PERSEPSI DAN PEMAHAMAN MAHASISWA UNIVERSITAS NEGERI SEMARANG TERHADAP PEDOMAN TRANSLITERASI ARAB LATIN - Nafis Amrullah; Akbar Syamsul Arifin (Bahasa dan Sastra Arab, Fakultas Adab dan Humaniora, UIN Sunan Gunung Djati, 2025)
Among students, transliteration is often used in writing papers, theses, or when reading Arabic texts that are difficult to read directly. Although there are transliteration standards from the Ministry of Religious Affairs, not all students have an adequate understanding of the rules of transliteration according to the standards. Many students still use transliteration freely and not based on official guidelines.This research uses a qualitative method with a descriptive analysis design. The data in this study are the answers of new students of the UNNES Arabic Education study program totaling 52 people. The researcher used a questionnaire as an instrument and source triangulation to test the validity of the data. Based on the results of this study, there are many letters that are still not recognized by the official transliteration. The letter Dal is the least recognized with a percentage of 6% and the letter Fa' is the most commonly recognized with a percentage of 100%. Among the advantages of using transliteration is the ease of understanding and pronouncing Arabic texts, as well as increasing confidence for beginner Arabic learners. Even so, this transliteration guideline provides an opportunity for beginner Arabic learners to facilitate understanding of Arabic texts. Keywords: Arabic Latin Transliteration, Student Perception, Arabic phonology